Surface matrix functionalization of ceramic-based membrane for oil-water separation: A mini-review - Raji, Y.O. (Springer, 2020)
Advanced filtration requires a cost-effective, highly efficient and environmentally friendly membrane fabrication to achieve excellent and extreme oleophobic and hydrophilic states with an appropriate surface functionalization approach. For an efficient oil-water separation, surface material and structure have been categorized as superoleophobic (high oil repellency) and superhydrophilic (strong affinity to water). This can be attributed to their selective mechanisms. In addition, it is very important to consider these key factors as they will imperatively provide a unique capability to exhibit surface roughness, stimulate low and high surface energy, and improve surface chemistry, which makes membranes function efficiently for the oil and water separation system. In this review article, the application of ceramic membrane for oily water treatment and the principle of superhydrophilic and superoleophobic ceramic membrane for oil-water separation are elaborated and, in addition, the current progress for the use of inorganic material to functionalize ceramic membrane surface based on physical and chemical methods is appraised. Finally, the challenges and outlook on the membrane for oily-water treatment are briefly examined. Â© 2020, The Korean Institute of Chemical Engineers.